Impact assessment of Integrated Pest Management (IPM) strategy for suppression of mango-infesting fruit flies in Kenya. (March 2016) - Muriithi, Beatrice W.; Affognon, Hippolyte D.; Diiro, Gracious M.; Kingori, Sarah W.; Tanga, Chrysantus M.; Nderitu, Peterson W.; Mohamed, Samira A.; Ekesi, Sunday
Abstract: We utilized two waves of data collected from a sample of mango farmers in Meru County in Kenya to evaluate the impact of Integrated Pest Management (IPM) strategy for controlling fruit flies in mango-production. We specifically explored the effect of five IPM practices including parasitoids ( p) and Metarhizium anisopliae -based biopesticides ( biop ), orchard sanitation ( os ), spot spray of food bait ( fb) and male annihilation technique ( mat ) on three outcome indicators: farmer pesticide expenditure, farm-level mango fruit yield losses and profit. We fitted difference-in-difference and household fixed effects regression models that account for unobserved heterogeneity across households. Our estimates differentiated the impact of the different IPM components, in comparison to farmers' practices as a control group. The descriptive statistics of the study show that application of the IPM strategy resulted in a 48% average increase in mango net income compared to the previous season irrespective of the IPM combination component used. The extent of improvement in net income, however, varied across treatments; treatments posfb and posmatfb registering the greatest improvements whereas the pos treatment generated the smallest increase in net income. The study findings further show mango yield losses due to fruit fly infestation reduced by an average of 19% among the IPM users. We also found a reduction in expenditure on pesticides, albeit across all the households. Regression model estimates show that, except for IPM combinations posbiop and pos, farmers using the rest of the IPM practices recorded significantly higher incomes from mango compared to their counterparts in the control group. We also noted that although average expenditure on pesticides decreased across all mango farmer households, the reduction was comparable between the treated and control farmer households. Our findings however, show significant decreases in mango damage due to fruit fly infestations among all farmers using the different IPM treatments. Our study recommends combinations of affordable and easy to apply and maintain IPM strategies that could yield significant impact on mango fruit fly control. Highlights: We assessed the impact of different combinations of IPM techniques for control of mango fruit flies. Outcome measures of interest are pesticide expenditure, yield losses and profits. We utilized household data, and applied difference-in-difference and fixed effects models. Mango income increased and losses reduced with different combinations of IPM techniques.